Laser-driven spin-exchange polarized deuterium target for the VEPP-3 storage ring; Polarized Beams and Polarized Gas Targets - Toporkov D. K.; Isaeva L. G.; Mishnev S. I.; Nikolenko D. M.; Popov S. G.; Rachek I. A.; Shestakov Yu.V.; Vesnovsky D. K.; Zevakov S. A.; Stibunov V. N. Victor Nikolaevich; Covlter K. P.; Gliman R.; et al. (1996, 1996)
В фонде НТБ ТПУ отсутствует